2008
DOI: 10.3168/jds.2007-0142
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the 5′ Upstream Region of the CXCR1 Chemokine Receptor Gene, and Their Association with Somatic Cell Score in Holstein Cattle in Canada

Abstract: Identification of regulatory elements in 5' regions of chemokine genes is fundamental for understanding chemokine gene expression in response to infection diseases. The CXCR1 receptor is expressed on the surface of neutrophils and interacts primarily with CXCL8 (IL-8), the most potent chemoattractant for neutrophils. The aim of this study was to characterize the 5' upstream region (2.1 kb) of the bovine CXCR1 chemokine receptor gene for polymorphism content and to identify in silico potential transcription-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 32 publications
(35 reference statements)
5
42
0
Order By: Relevance
“…Beecher et al (2010) revealed the association of the G allele with reduced SCS in cows of five breeds, but not in Holstein-Friesian bulls. The influence of mutation +735C>G on mastitis evaluated based on SCS was not confirmed neither by Leyva-Baca et al (2008) nor by Goertz et al (2009). Likewise, Verbeke et al (2012) did not find any association between the identified CXCR1 gene polymorphism and SCC.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Beecher et al (2010) revealed the association of the G allele with reduced SCS in cows of five breeds, but not in Holstein-Friesian bulls. The influence of mutation +735C>G on mastitis evaluated based on SCS was not confirmed neither by Leyva-Baca et al (2008) nor by Goertz et al (2009). Likewise, Verbeke et al (2012) did not find any association between the identified CXCR1 gene polymorphism and SCC.…”
Section: Resultsmentioning
confidence: 81%
“…Some authors demonstrated an association between CXCR1 gene polymorphism and udder health, evaluated using various parameters (e.g., SCS, somatic cell scores) (Youngerman et al, 2004a;Beecher et al, 2010;Galvão et al, 2011), but others (e.g., Leyva-Baca et al, 2008, Goertz et al, 2009) rejected this hypothesis. Recent studies have indicated a high degree of polymorphism in the CXCR1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups studied associations between SNP in CXCR1 and udder health (Youngerman et al, 2004;Leyva-Baca et al, 2008b;Goertz et al, 2009;Beecher et al, 2010;Galvão et al, 2011;Verbeke et al, 2012). However, we were the first to study pathogenspecific data in a relative large population from multiple commercial dairy herds.…”
Section: Discussionmentioning
confidence: 99%
“…But no report is available regarding SNP in buffalo yet. SNP (one) in the coding region (Youngerman et al 2004) and one SNP in the 5' upstream region (Leyva-Baca et al, 2008) of CXCR1 were found to be associated with mastitis susceptibility in case of Holstein Cattle. Zhou et al (2013) detected 4 single nucleotide polymorphisms (SNPs) of the CXCR1 gene in Chinese native cattle and found the significant association of c.337A>G and c.365C>T with the somatic cell score, which suggests the possible role of these SNPs in the host response against mastitis.…”
Section: Resultsmentioning
confidence: 99%